2011
DOI: 10.1109/tie.2010.2043041
|View full text |Cite
|
Sign up to set email alerts
|

Cascaded DC–DC Converter Photovoltaic Systems: Power Optimization Issues

Abstract: This paper investigates the issues of ensuring global power optimization for cascaded dc-dc converter architectures of photovoltaic (PV) generators irrespective of the irradiance conditions. The global optimum of such connections of PV modules is generally equivalent with performing the maximum power point tracking (MPPT) on all the modules. The most important disturbance occurs when the irradiance levels of modules happen to be sensibly different from a module to another-in this case, voltage-limitation requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
134
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(137 citation statements)
references
References 27 publications
1
134
0
Order By: Relevance
“…A weighting factor based strategy similar to the present work was reported e.g. in [8]. The weighting factor was solely based on different radiation conditions where the only variable parameter was solar irradiation factor.…”
Section: Index Terms-cascadedmentioning
confidence: 96%
See 2 more Smart Citations
“…A weighting factor based strategy similar to the present work was reported e.g. in [8]. The weighting factor was solely based on different radiation conditions where the only variable parameter was solar irradiation factor.…”
Section: Index Terms-cascadedmentioning
confidence: 96%
“…A previous study on this area suggested a cascaded approach over the parallel approach from reliability and cost perspective [6]. Apart from the reliability/cost issues, the parallel approach has other drawbacks in conjunction with low voltage energy sources [7], [8] such as: a) low converter efficiency (e.g. < 90%) due to the extremely high step-up ratio (10 -20) required to meet the full dc-link voltage of the inverter, b) increased high frequency current ripple on the inductor and on the battery side, c) reduced switch utilisation, d) greater effect on control coming from the system parasitic at a high converter duty ratio and e) increased the size and cost of the overall converter to attain a high efficiency.…”
Section: Index Terms-cascadedmentioning
confidence: 99%
See 1 more Smart Citation
“…This converter is used as an interface between PV generator and the load in order to extract maximum power and thus making the generator on its maximum power point (MPP). The DC-DC converter is controlled by an MPPT algorithm (maximum power point tracking) [1] [2]. Maximum power point tracking is a mechanism which can guarantee the maximal power permanently [3].…”
Section: Introductionmentioning
confidence: 99%
“…PV installations are growing day to day either as residential stand alone or grid connected. It is necessary to enhance the efficiency of a PV system irrespective irradiance and temperature the PV system should contain some form controller which is responsible for an optimization to extract maximum power from the panel, The major existing work done in this field is to find simple and efficient method to extract maximum power [1,4] where analysis done with different irradiance and temperature. Several methods are proposed [5,7] to extract maximum power and compared with their techniques performance are analysed by different authors.…”
Section: Introductionmentioning
confidence: 99%